The phenomenon of urbanisation from a public health perspective. Urban spaces as a possible source of epidemics and pandemics caused by an infectious disease - Pruszyński, Jacek; Kocik, Janusz; Pruszyńska, Irena; Cianciara, Dorota; Sękowski, Kuba; Włodarczyk-Pruszyńska, Inga (Journal of Education, Health and Sport, 2023)
Introduction Urbanisation is a global process leading to development of urban infrastructure and thus an increase in the population of urban areas. Health threats, including epidemics of infectious diseases that may break out in growing urban areas, can spread quickly and their effects could spread outside of the local territory. Purpose To outline the relationship between globalising, post-modern urbanisation processes, in particular the specific form of extended urbanisation, and the risks posed by infectious diseases that could give rise to new epidemics or pandemics. State of knowledge Health risks occurring at the local level of an urban area react to, and simultaneously affect, health situation occurring at an indefinite distance from the original site of the event. An important impact on the situation are the expanding or newly emerging urban areas, which cause negative changes in social conditions, and the increase in spatial mobility of the global population, which facilitates the spread of infectious diseases. Summary Understanding 21st century urban trends is the key to improving collective health. Adopting a "public health perspective" regarding values and attitudes towards social phenomena and reality, as well as the necessary methods of conduct, seems to be one of the main challenges of the current era in which people around the world, regardless of the country's development status and level of resources, currently live in within one “ecosystem of infectious diseases”. Planned and controlled urbanization, taking into account the achievements of modern epidemiology, including molecular epidemiology, will help will help along the remediation of the cities of the future.